O debate toleracionista a partir de More, Locke, Mill, Marcuse e Walzer: história, problemas e novas perspectivas - Diniz, Márcio Victor de Sena (2018)
The present master’s thesis analyzes the debate on tolerance by means of three main points chosen due to their modern day relevance: i) the conceptual problem of the polysemy of the term; ii) the methodological problem of the typology of tolerance and the relationship established between its different types; iii) the practical problem of the limits. This thesis argues that, despite considerably constructive results obtained over the course of its existence, throughout history, the discussion on tolerance has presented two major misconceptions that have prevented a more efficient development of the debate: that of the conceptual confusion and that of the terminological inaccuracy. Therefore, a logic-linguistic analysis applied to the concept of tolerance is proposed with the aim of elucidating both misconceptions, and as a result find new ways to solve the aforementioned problems. The thesis is divided into seven chapters, with the initial four chapters examining six major works of the debate on tolerance, which are the following: Thomas More’s Utopia (Chapter One); John Locke’s A Letter Concerning Toleration (Chapter Two); John Stuart Mill’s On Liberty and The Subjection of Women (Chapter Three); Herbert Marcuse’s Repressive Tolerance and Michael Walzer’s On Toleration (Chapter Four). In Chapter Five, the necessity of properly defining each meaning of the term tolerance is discussed by presenting the Thesis of Adequate Meanings and Inadequate Meanings (TA), the Thesis of Opposite Definitions (TDO) and the Thesis of Irreducibility (TI). The chapter also analyses their logico-conceptual impacts on the debate on tolerance. Chapter 6 starts with a detailing of the Thesis of Compatibility and Incompatibility (TCI) applied to the types of tolerance and how this thesis can offer an alternative solution to the problem of typology. Next, the resulting concepts of the TA and TCI are used to examine a few legal documents related to the debate (UNESCO’s Declaration of Principles on Tolerance and the Brazilian laws No. 7.716/89 and No. 9.459/97). Finally, Chapter 7 revolves around the issue of limits of tolerance. The TA and TCI are applied to the previously mentioned texts by Locke and Stuart Mill, and to an event that occurred in Brazil (the “Mein Kampf affair”) that is relevant to the discussion. The aim is to show that a possible solution to the practical problem of limits is tied to the answers to both the conceptual problem of the polysemy and the methodological problem of the typology.